The Political Impact of Dutch Colonial Ethnic Spatial Planning on the Territorial Fragmentation and Existence of the Pakpak Tribe (1842-1942) - Anna Martyna Sinamo; Singgih Tri Sulistiyono; Haryono Rinardi (Indonesian Historical Studies, 2025)
This article examines the political impact of ethnic spatial planning implemented by the Dutch Colonial government on the existence of the Tapanuli Residency in the Onder Afdeling Pakpak Landen from 1842 to 1942. This study employs the historical method, which includes the heuristic, criticism, interpretation, and historiography stages, and is supported by a sociological approach to analyze social structure and changes. The results show that the establishment of the Tapanuli Residency, as a concrete manifestation of colonial ethnic spatial planning policy, was deliberately designed to divide, separate, and weaken the power of ethnic groups to make them easier to monitor and control. This penetration policy resulted in the fragmentation of the territory of Tanoh Pakpak, which was originally a unified cultural and customary entity based on clan land ownership, into five customary regions (Pakpak Silima Suak). As a result of this ethnic spatial arrangement, the customary territory of Pakpak Silima Suak experienced a highly significant reduction and was administratively split into three different residencies. The Kelasen region was integrated into Batak Landen, Tongging into the East Sumatra Residency, and Boang into Singkil in the Aceh Residency. This fragmentation left the Onder Afdeling Pakpak Landen area consisting of only three suak, namely Suak Pegagan, Suak Keppas, and Suak Simsim. The political impact of this ethnic spatial policy not only weakened the political existence of the Pakpak people at the local level but also degraded their traditional leadership system. The abolition of customary leaders' roles such as the takal aur and pertaki, replaced by the colonial bureaucracy, ultimately threatened the existence of the Pakpak people and triggered deep social, cultural, and economic marginalization in their own ancestral land